2004
DOI: 10.1126/science.1092712
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Replication ofListeria monocytogenesin the Murine Gall Bladder

Abstract: The bacterium Listeria monocytogenes can cause a life-threatening systemic illness in humans. Despite decades of progress in animal models of listeriosis, much remains unknown about the processes of infection and colonization. Here, we report that L. monocytogenes can replicate in the murine gall bladder and provide evidence that its replication there is extracellular and intraluminal. In vivo bioluminescence imaging was employed to determine the location of the infection over time in live animals, revealing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
222
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(234 citation statements)
references
References 15 publications
9
222
2
1
Order By: Relevance
“…A recent report using in vivo bioluminescence imaging took advantage of an L. monocytogenes expressing a luxkan transposon cassette. This study elegantly demonstrated active extracellular bacterial growth and replication in the gall bladder for several days after oral and intravenous infection of mice [27]. This surprising result suggests that the gall bladder promotes bacterial growth and systemic colonization, whatever the route of infection.…”
Section: The Importance Of the Route And Dose Of Infectionmentioning
confidence: 60%
“…A recent report using in vivo bioluminescence imaging took advantage of an L. monocytogenes expressing a luxkan transposon cassette. This study elegantly demonstrated active extracellular bacterial growth and replication in the gall bladder for several days after oral and intravenous infection of mice [27]. This surprising result suggests that the gall bladder promotes bacterial growth and systemic colonization, whatever the route of infection.…”
Section: The Importance Of the Route And Dose Of Infectionmentioning
confidence: 60%
“…This is exemplified by the decrease in luminescence that has been observed when many luxexpressing bacterial species, such as Bifidobacterium, 38 enter stationary phase during in vitro growth. [46][47][48] Bioluminescent bacteria have been used extensively to study a diverse range of biological processes such as infection, 49 quorum sensing 50 and gene expression. 51 However, the employment of luciferase or lux tagged bacterial strains as gene delivery vehicles for the treatment of cancer is an emerging field.…”
Section: Bioluminescence Imaging (Bli)mentioning
confidence: 99%
“…Indeed, a number of researchers have described attenuation in lux-and GFPexpressing strains. 47,[75][76][77] Maximizing reporter expression. Bacterial reporter gene expression is exquisitely dependent on transcriptional and translational signals.…”
Section: Instrumentation For Oimentioning
confidence: 99%
“…The focal signal observed in the lower thorax originated from the gallbladder. L. monocytogenes replicates in the lumen of this organ after either intravenous or oral infection (10). Miscarriage occurred in some animals in the 5 × 10 5 CFU group on day 4 postinfection (at E18).…”
Section: Bli Of Transplacental Infectionmentioning
confidence: 98%
“…The construction of the bioluminescent L. monocytogenes strain 2C from the parental L. monocytogenes strain 10403S has been described (10). For a description of the strain, see Supplemental Methods online.…”
Section: In Vivo Blimentioning
confidence: 99%